Current Ratio, Earnings Per Share, Extensible Business Reporting Language, dan Price To Book Value - Fatoniaji, Wildany Ilham; Mimba, Ni Putu Sri Harta (E-Jurnal Akuntansi, 2023)
One of the indicators used by investors to carry out investment analysis is Price to Book Value (PBV) which is influenced by financial performance and ease of access to company information. This research aims to determine the effect of Current Ratio (CR), Earnings per Share (EPS) and Extensible Business Reporting Language (XBRL) on Price to Book Value (PBV). The population of this study are companies that have been listed on the KOMPAS100 index during the 2012-2017 period. The sample selection was carried out by purposive sampling method. The sample chosen was 10 companies. The data is taken from the official website of the Indonesia Stock Exchange. Data is processed using multiple linear regression models. The results of this study state that CR has no significant effect on PBV, EPS has a positive and significant effect on PBV, and XBRL has a negative and significant effect on PBV. Keywords: Current Ratio; Earnings per Share; Extensible Business Reporting Language; Price to Book Value